Perfil clínico e funcional de pacientes com esclerose múltipla : impacto sobre a força muscular, a qualidade de vida e a função pulmonar - Tarnhovi, Evandro Gonzalez (2016)
INTRODUCTION: Studies investigating health determinants in subjects with multiple sclerosis (MS) are mostly focused on associating a few clinical parameters, ignoring certain social and bio-psychological factors that can potentially exert influence. OBJECTIVES: The aim of this Ph.D. thesis was to investigate the impact of disease severity on muscular strength, quality of life and pulmonary function in mild to advanced stages subjects with MS. METHODS: Forty-six subjects diagnosed with MS were included in this trial, being 17 in the mild stage of the disease (G1), 24 in the moderate stage (G2) and 5 in the advanced stage of the disease (G3). A specific instrument that assess quality of life in MS was applied in all participants. Handgrip force was included to investigate muscular strength of the subjects. Pulmonary function was assessed with a spirometer and an impulse oscillometer. For the statistical analysis, we used one-way analysis of variance to compare groups for the variables that contemplated the parametric assumptions, and the Kruskal Wallis test for those variables that did not contemplated the parametric assumptions. Paired comparisons were done with Tukey post-hoc. Significance was set at 5% (p<.05). RESULTS: The data showed statistical differences between groups for quality of life (p=.017), muscular strength (p=.001) and spirometry (p=.035). Paired comparisons demonstrated the impact of disease severity on such factors (p<.05) There was no interference of the disease on the measures of the impulse oscillometer (p=.413). CONCLUSION: This Ph.D. thesis proved the impact of disease severity on quality of life, on muscular strength and on spirometry in individuals with mild to advance stages of MS. Differently, MS did exert any impact on measures of impuse x oscillometry. Further studies should focus their analyses on MS to find ways to control these predictors and keep quality of life similar to healthy peers.